Pengaruh Kompensasi Dan Pengembangan Karir Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening Pada Bank SUMSEL BABEL Syariah Kc Palembang - Selly Ardelia; Hilda; Fakhrina (Jurnal Ekonomi dan Bisnis Digital, 2022)
Every company will always try to improve employee performance, with the hope that the company’s goals will be achieved. The theory used is the theory of human resource management. This study aims to determine whether compensation, career development, and motivation as intervening variables affect employee performance at Bank Sumsel Babel Syariah KC Palembang. The method used in this research is a quantitative method. The data collection technique was carried out by distributing questionnaires using a Likert scale. The sample in this study were 37 respondents with a sampling technique using the saturated sample method. The data analysis techniques used in this study are validity and reliability tests, classic assumption tests, multiple linear regression analysis, path analysis, and hypothesis testing by processing data using SPSS version 26. The research results show that compensation (X1) t count>t table (10.572>2.032) has a positive and significant effect on employee performance, career development(X2) t count>t table (3.230>2.032) has a positive and significant effect on employee performance, compensation (X1) t count>t table (2.548>2.032) positive and significant effect on motivation, career development (X2) t count>t table (2,521>2.032) positive and significant effect on motivation, motivation (Z) t count>t table (28.866>2.032) positive and significant effect on employee performance, compensation (X1) for motivation (Z) resuluts of direct influence < indirect influence means that it has a effect on employee performance, career development (X2) for motivation (Z) result of direct influence< indirect influence means that it has a effect on employee performance. Suggestions in this study, it is hoped that Bank Sumsel Babel Syariah KC Palembang pays more attention to the placement of employees and the compensation given to employees.